Drinking alcohol to cope with hyperactive ADHD?: Self-reports vs. continuous performance test in patients with ADHD and/or alcohol use disorder - Luderer, Mathias; Seidt, Johanna; Gerhardt, Sarah; Hoffmann, Sabine; Vollstädt-Klein, Sabine; Reif, Andreas; Sobanski, Esther (Frontiers in psychiatry, 2023)
Rationale: Attention deficit/hyperactivity disorder (ADHD) is common in alcohol use disorder (AUD). Continuous performance tests (CPTs) allow to measure ADHD related deficits in a laboratory setting. Most studies on this topic focused on CPTs measuring inattention or impulsivity, disregarding hyperactivity as one of the core symptoms of ADHD. Methods: We examined N = 47 in three groups (ADHD N = 19; AUD N = 16; ADHD + AUD N = 12) with questionnaires on ADHD core symptoms, executive functioning (EF), mind wandering, and quality of life (QoL). N = 46 (ADHD N = 16; AUD N = 16; ADHD + AUD N = 14) were examined with a CPT (QbTest®) that also measures motor activity objectively. Results: Inattention and impulsivity were significantly increased in AUD vs. ADHD and in AUD vs. ADHD + AUD. Hyperactivity was significantly higher in ADHD + AUD vs. ADHD and ADHD + AUD vs. AUD, but not in ADHD vs. AUD. EF was lower in both ADHD groups vs. AUD. Mind wandering was increased in both ADHD groups vs. AUD. QoL was significantly lower in ADHD + AUD compared to AUD. In contrast, results of the QbTest were not significantly different between groups. Conclusion: Questionnaires are more useful in assessing ADHD core symptoms than the QbTest®. Hyperactivity appears to be a relevant symptom in ADHD + AUD, suggesting a possible pathway from ADHD to AUD. The lower QoL in ADHD + AUD emphasizes the need for routine screening, diagnostic procedures and treatment strategies for this patient group.
Gesehen am 15.08.2024